Flowering date of taxonomic families predicts phenological sensitivity to temperature: Implications for forecasting the effects of climate change on unstudied taxa1. Issue 7 (1st July 2013) - Mazer, Susan J.; Travers, Steven E.; Cook, Benjamin I.; Davies, T. Jonathan; Bolmgren, Kjell; Kraft, Nathan J. B.; Salamin, Nicolas; Inouye, David W.
Abstract : Premise of the study: Numerous long‐term studies in seasonal habitats have tracked interannual variation in first flowering date (FFD) in relation to climate, documenting the effect of warming on the FFD of many species. Despite these efforts, long‐term phenological observations are still lacking for many species. If we could forecast responses based on taxonomic affinity, however, then we could leverage existing data to predict the climate‐related phenological shifts of many taxa not yet studied. Methods: We examined phenological time series of 1226 species occurrences (1031 unique species in 119 families) across seven sites in North America and England to determine whether family membership (or family mean FFD) predicts the sensitivity of FFD to standardized interannual changes in temperature and precipitation during seasonal periods before flowering and whether families differ significantly in the direction of their phenological shifts. Key results: Patterns observed among species within and across sites are mirrored among family means across sites; early‐flowering families advance their FFD in response to warming more than late‐flowering families. By contrast, we found no consistent relationships among taxa between mean FFD and sensitivity to precipitation as measured here. Conclusions: Family membership can be used to identify taxa of high and low sensitivity to temperature within the seasonal, temperate zone plant communities analyzed here. The high sensitivity of early‐flowering families (and the absence of early‐flowering families not sensitive to temperature) may reflect plasticity in flowering time, which may be adaptive in environments where early‐season conditions are highly variable among years.